Pulmonary alveolar proteinosis or coronavirus disease 19 pneumonia: A clinical case study - Hashemi, Huriyeh; Mozafari, Amir Mohamad; Etemadi Toudeshki, Nahid; Pourabdollah Toutkaboni, Mihan; Naderi, Zohre (Journal of Shahrekord University of Medical Sciences, 2025)
The COVID-19 pandemic has resulted in a significant number of hospitalizations worldwide, complicating the diagnosis of rare respiratory diseases, such as pulmonary alveolar proteinosis (PAP), which can present with clinical symptoms and radiological findings similar to those of COVID-19. Consequently, accurate diagnosis is crucial. This report describes a case involving a young man with a history of progressive shortness of breath who was initially treated for COVID-19 pneumonia based on high-resolution computed tomography (HRCT) findings. However, following three negative polymerase chain reaction tests from the patient’s throat swab and a lack of clinical improvement despite COVID-19 treatment, he underwent bronchoscopy and bronchoalveolar lavage. The results of these procedures demonstrated PAP. Given that COVID-19 presents with a wide range of manifestations and that HRCT of the lungs is currently the most sensitive diagnostic test for the disease, it is essential to consider the patient’s medical history when diagnosing various pulmonary conditions. More precisely, a thorough assessment of the patient’s history can significantly influence the diagnostic outcome.